The role of quick Sepsis-related Organ Failure Assessment score as simple scoring system to predict Fournier gangrene mortality and the correlation with Fournier's Gangrene Severity Index: Analysis of 69 patients - Bambang S. Noegroho; Kuncoro Adi; Akhmad Mustafa; Rais Syaeful Haq; Zola Wijayanti; Jason Liarto (Asian Journal of Urology)
Objective: Fournier's gangrene is a rare but life-threatening infection disease with high mortality rate. The quick Sepsis-related Organ Failure Assessment (qSOFA) is a new and simpler scoring system that may identify patients with suspected infection who are at greater risk for a poor outcome. The purpose of this study was to find out role of qSOFA in determining prognosis of Fournier's gangrene patients. Methods: This study is a case control with retrospective review of Fournier's gangrene patients treated at Hasan Sadikin Hospital from January 2013 to December 2017 who met inclusion criteria. Participants were divided into two groups according to qSOFA score as high qSOFA (2–3) and low qSOFA (0–1). Results: From 69 patients, the mortality rate was 24.6%. The sensitivity of qSOFA score to predict mortality was 88.2%; the specificity was 94.2%; positive predictive value was 83.3%; negative predictive value was 96.1%; positive likelihood ratio was 15.2; negative likelihood ratio was 0.12; and the area under the receiver operating characteristic curve of qSOFA was 94.2%. There was significant association between qSOFA scale and mortality with p-value of 0.0001. The qSOFA score has strong positive correlation with Fournier's Gangrene Severity Index (p<0.0001, r=0.704). Conclusion: qSOFA scoring system has a high prognostic value and can be used to determine prognosis of Fournier's gangrene patients.